Androgen-deprivation therapy impairs left ventricle functions in prostate cancer patients - ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; ŞENER, TARIK EMRE (SPRINGER, 2019)
BackgroundAndrogen-deprivation therapy (ADT) is a treatment option for locally advanced and metastatic prostate cancer (PCA). The aim of the study was to evaluate the effect of ADT on left ventricular (LV) functions assessed by speckle-tracking echocardiography (STE) in prostate cancer (PCA) patients.MethodsForty-nine consecutive PCA patients (mean age 71.56.7years) who would be treated with radiotherapy and ADT and 32 consecutive PCA patients (mean age 71.97.0years) who would be treated with radical or partial prostatectomy and 42 age-matched healthy men (mean age 70.5 +/- 9.1years) were included in our study. The left ventricular functions were assessed by both conventional echocardiography and STE at baseline and 6months later.ResultsThere were not any significant difference in characteristics of the patients and controls. There were not any significant differences in conventional echocardiographic measures at baseline and at 6th month among the PCA patients and controls. Although there were not any significant differences in STE measures at baseline among the PCA patients and controls, the strain measures of the PCA patients receiving ADT decreased significantly at the 6th month and were significantly lower compared to strain measures of PCA patients undergoing prostatectomy and controls. There was not any statistically significant difference in baseline and 6th-month strain measures of the PCA patients undergoing prostatectomy.Conclusions<ADT might be associated with decrease in LV longitudinal, circumferential, and radial strain measures in patients with PCA. STE might be useful for early identification of LV subclinical impairment in PCA patients treated with ADT.
Keywords: Androgen-deprivation therapy; Echocardiography; Prostate cancer; Testosterone; AMERICAN SOCIETY; EUROPEAN ASSOCIATION; TESTOSTERONE; ECHOCARDIOGRAPHY; RECOMMENDATIONS; MORTALITY; STEROIDS; UPDATE; MEN